Empowerment of love for Jane Austen's Females: a case of creativity in familiarity - Alhasan, Assia; Omar, Noritah (Arab World English Journal, 2020)
The goal of this qualitative study is to explore unfamiliar concepts presented in familiar contexts in Austen’s Pride and Prejudice (1813) and Mansfield Park (1814). Also, it intends to examine Austen's creativity in unfamiliar concepts such as women's freedom of choice and education from a feminist perspective. This study is significant for shedding light on the empowerment of love decision, females’ self-awareness and women’s voice presented in conventional systems. In addition, it will help feminists to figure out the feminism issues reflected in Austen's work. Further, this study addresses the question of unfamiliar concepts in Austen’s familiar contexts and identify the impact of decision making on women’s equality. The researcher uses textual analysis to discuss main themes and address research questions. The findings of the study show that Austen best novels preached out women's emancipation of so-called marriage-market. Also, the result indicates that women of her time postulated love in marriage for achieving self- recognition and self-esteem through creative technique of familiarizing unfamiliar concepts. Therefore, it introduces new thread to Austen studies by examining how Austen familiarized her readers unconsciously with modern concepts at the late 18th century in societal and cultural respects. This study recommends that further investigations be conducted in this regard.